The shaping of onion seedlings performance through substrate formulation and co-inoculation with beneficial microorganism consortia - Pokluda, Robert; Ragasová, Lucia Nedorost; Jurica, Miloš; Kalisz, Andrzej; Komorowska, Monika; Niemiec, Marcin; Caruso, Gianluca; Gąstoł, Maciej; Sekara, Agnieszka (Frontiers in Plant Science, 2023)
Smart management in crop cultivation is increasingly supported by application of arbuscular mycorrhizal fungi (AMF) and plant growth-promoting microorganisms (PGPM), which sustain soil fertility and plant performance. The aim of this study was the evaluation of the effects of consortia composed of AMF (Claroideoglomus claroideum BEG96, Claroideoglomus etunicatum BEG92, Funneliformis geosporum BEG199, Funneliformis mosseae BEG 95, and Rhizophagus irregularis BEG140) and PGPM (Azospirillum brasilense -AZ, or Saccharothrix sp. -S) on onion cultivated in growing media with a composition corresponding to a degraded soil. Three types of substrate formulations were used, with peat:sand ratios of 50:50, 70:30, 100:0 (v:v). The analysis of substrate parameters crucial for its fertility (pH, salinity, sorption complex capacity, and elements' content) and characteristics reflecting onion seedlings' performance (fresh weight, stress biomarkers, and elements' content) was performed. AMF colonized onion roots in all treatments, showing increasing potential to form intercellular structures in the substrates rich in organic matter. Additionally, co-inoculation with PGPM microorganisms accelerated arbuscular mycorrhiza establishment.Increased antioxidant activity and glutathione peroxidase (GPOX) activity of onion roots sampled from the formulations composed of peat and sand in the ratio of 100:0, inoculated with AMF+S, and positive correlation between GPOX, fresh weight and antioxidant activity of onion roots reflected the successful induction of plant acclimatization response. Total phenols content was the highest in roots and leaves of onion grown in substrates with 70:30 peat:sand ratio, and, in the case of roots, it was correlated with AMF colonization parameters but not with antioxidant activity. AMF and PGPM efficiency in supporting onion growth should be linked to the increased onion root system capacity in mineral salts absorption, resulting in more efficient aboveground biomass production. AMF and PGPM consortia were effective in releasing minerals to soluble fraction in substrates rich in organic matter, making elements available for uptake by onion root system, though this phenomenon depended on the PGPM species. Microorganism consortia enhanced onion seedlings' performance also in substrates with lower content of organic carbon through plant biofertilization and phytostimulation.